PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI, DAN KESESUAIAN KOMPENSASI TERHADAP KECENDERUNGAN KECURANGAN (FRAUD) AKUNTANSI PADA LEMBAGA PERKREDITAN DESA SEKECAMATAN KERAMBI - Ni Kadek Rai Yusada Sari (UNHI Press, 2022)
Accounting fraud is an act of planned fraud by violating accounting rules carried out by a person or group of people in order to obtain personal or group benefits that can harm many other parties. The purpose of this research is to see how effective internal control, adherence to accounting rules, and compensation suitability affect the likelihood of accounting fraud at Lembaga Perkreditan Desa (LPD) in Kerambitan District. All personnel of Kerambitan District LPDs were included in this survey, and the responses were 78 people, including the Head of LPD, Administration, and Treasurer. The purposive sampling methodology was employed to determine the sample. Based on the findings of this study, the effectiveness of internal control and compliance with accounting rules has a significant negative effect on the tendency of accounting fraud, while significantly adjusting for compensation that does not affect accountants’ fraud tendencies